MANAJEMEN PEMERINTAHAN DINAS PARIWISATA DAN KEBUDAYAAN DALAM PENGELOLAAN KAMPUNG BUDAYA DI KABUPATEN KARAWANG - Syifa Fauzia Rohman; Dadan Kurniansyah; Rachmat Ramdani (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
Problems regarding the management of the Cultural Village include the lack of careful planning, lack of human resources, capital and infrastructure, lack of coordination and leadership and have not been felt by the community and have not been able to contribute to the PAD of Karawang Regency. The results of this study indicate that government management in the management of Kampung Budaya is still not optimal. In terms of planning, Disparbud does not have a plan that has not been stated in the Strategic Plan. The sub-function of organizing resources is not yet optimal, which has not been marked by the lack of natural resources, human resources and natural resources. The sub-function of resource use is not yet optimal, which is indicated by the lack of government communication, government and government coordination. In terms of control, the government has not been able to carry out control optimally, marked by the lack of maximum supervision carried out by the Department of Tourism and Culture of Karawang Regency.